Structural Dynamics of Bridges Under the Coupling Effect of Windmills and Bridges - Huang, Guoqing; Ren, Na; Zheng, Hengbin (European Journal of Computational Mechanics, 2023)
To analyze the coupled dynamics effects of existing railroad frame bridge structures under the action of traffic, a coupled train-ballast track-suspension bridge girder-soil dynamics model is established based on railroad large system dynamics and finite element theory. The joint ABAQUS-MATLAB simulation, time-varying coupling, and multi-step dynamic iterative solution strategies are introduced to numerically simulate the mechanical properties of existing railroad structures under the coupled effects of wind loads and traffic action. Specifically, (1) a dichotomous method is proposed to investigate the static behavior of the bridge in the bridge-forming state, and the maximum upper arch of the stiffened girder is 3.67 cm, which occurs at about 1/4 and 3/4 positions of the main span, and the lower deflection of the side span is larger, and the maximum lower deflection occurs at 11.04 cm in the span of the 110 m side span. The vertical acceleration in the span increases immediately with the maximum peak of 30 cm/s2, while the lateral acceleration is maintained within 20 cm/s22. (2) The effects of the stiffness of the rail fasteners and the bridge plate support stiffness on the dynamics were studied. (3) The results of the time-domain analysis are in general agreement with the simulation data, except for the error of the ambient vibration background existing at the peak. The correctness of the simulation model is verified.